The impact of digital transformation on the operational efficiency of commercial banks: Empirical evidence from Vietnam - Nguyen, Huyen Thanh; Nguyen, Giang Huong; Tran, Yen Thi Hai (International Journal of Innovative Research and Scientific Studies, 2025)
In recent years, the rapid development of digital transformation has reshaped the landscape of the banking sector, particularly in emerging economies like Vietnam. This study examines the impact of digital transformation on the operational efficiency of commercial banks in Vietnam, analyzing how digitalization initiatives such as mobile banking, artificial intelligence, data analytics, and automation contribute to improved service quality, cost reduction, and overall productivity. Using a combination of quantitative and qualitative data, the study evaluates key performance indicators (KPIs) from a range of commercial banks in Vietnam to identify significant patterns and outcomes related to digital innovation. Findings reveal that digital transformation has led to notable increases in customer satisfaction, operational speed, and cost efficiency, though challenges remain in areas such as cybersecurity and the adaptation of legacy systems. The study offers insights and strategic recommendations for Vietnamese banks to optimize digital solutions and achieve sustainable growth in a competitive market environment.